Comparative Assessment of E-cadherin's Expression between the Metastatic and Non-metastatic Oral Squamous Cell Carcinoma: An Immunohistochemical Study - Sufia Khan; Veda Hegde; Deepti Shrivastava; Mohammed Azamulla; Mohammad Khursheed Alam; Kumar Chandan Srivastava (Association of Support to Oral Health Research (APESB), 2023)
Objective: To identify the clinicopathological correlation of E-cadherin expression in metastatic and non-metastatic oral squamous cell carcinoma (OSCC). Material and Methods: A total of 90 paraffin-embedded tissue sections of OSCC were retrieved from the registry. The total selected samples were 45 cases each from the primary lesions of metastatic and non-metastatic OSCC. One section was subjected to routine Hematoxylin and eosin stain and another to immunohistochemical analysis for E-cadherin expression. Results: A non-significant (p˃0.05) increased expression is seen in the non-metastatic group compared to the metastatic group, with predominantly membrane as the staining site in either group. However, the expression of E-cadherin did not reveal any statistically significant association with independent variables such as age, gender, and adverse habits of the patients (p>0.05). On the other hand, with respect to the histological differentiation of OSCC, a significant association (p<0.001) was observed with the well-differentiated type of metastatic OSCC. Conclusion: E-cadherin was useful to some extent in predicting regional metastasis. However, further studies using a panel of biomarkers with increased sample size may help us understand the process involved in metastasis.